Mechanical Performance of Extensive Restorations Made with Short Fiber-Reinforced Composites without Coverage: A Systematic Review of In Vitro Studies - Jakab, András (Switzerland, 2025)
In recent years, composite resin materials have been the most frequently used materials for direct restorations of posterior teeth. These materials have some clinically relevant limitations due to their lack of fracture toughness, especially when used in larger cavities with high volume factors or when utilized as direct or indirect overlays or crown restorations. Recently, short-fiber-reinforced composite materials have been used in bi-structure restorations as a dentine substituting material due to their superior mechanical properties; however, there is no scientific consensus as to whether they can be used as full restorations. The aim of our review was to examine the available literature and gather scientific evidence on this matter. Two independent authors performed a thorough literature search using PubMed and ScienceDirect up until December 2023. This study followed the PRISMA guidelines, and the risk of bias was assessed using the QUIN tool. The authors selected in vitro studies that used short-fiber-reinforced composite materials as complete restorations, with a conventional composite material as a comparison group. Out of 2079 potentially relevant articles, 16 met our inclusion criteria. All of the included studies reported that the usage of short-fiber-reinforced composites improved the restoration’s load-bearing capacity. Fifteen of the included publications examined the fracture pattern, and thirteen of them reported a more favorable fracture outcome for the short-fiber-reinforced group. Only one article reported a more favorable fracture pattern for the control group; however, the difference between groups was not significant. Within the limitations of this review, the evidence suggests that short-fiber-reinforced composites can be used effectively as complete restorations to reinforce structurally compromised teeth.